Visualizing Mutation-Specific Differences in the Trafficking-Deficient Phenotype of Kv11.1 Proteins Linked to Long QT Syndrome Type 2 - Hall, Allison R.; Anderson, Corey L.; Smith, Jennifer L.; Mirshahi, Tooraj; Elayi, Claude S.; January, Craig T.; Delisle, Brian P. (Frontiers in Physiology, 2018)
Abstract KCNH2 encodes the Kv11.1 α-subunit that underlies the rapidly activating delayed-rectifier K+ current in the heart. Loss-of-function KCNH2 mutations cause long QT syndrome type 2 (LQT2), and most LQT2-linked missense mutations inhibit the trafficking of Kv11.1 channel protein to the cell surface membrane. Several trafficking-deficient LQT2 mutations (e.g. G601S) generate Kv11.1 proteins that are sequestered in a microtubule-dependent quality control (QC) compartment in the transitional endoplasmic reticulum (ER). We tested the hypothesis that the QC mechanisms that regulate LQT2-linked Kv11.1 protein trafficking are mutation-specific. Confocal imaging analyses of HEK293 cells stably expressing the trafficking-deficient LQT2 mutation F805C showed that, unlike G601S-Kv11.1 protein, F805C-Kv11.1 protein was concentrated in several transitional ER subcompartments. The microtubule depolymerizing drug nocodazole differentially affected G601S- and F805C-Kv11.1 protein immunostaining. Nocodazole caused G601S-Kv11.1 protein to distribute into peripheral reticular structures, and it increased the diffuse immunostaining of F805C-Kv11.1 protein around the transitional ER subcompartments. Proteasome inhibition also affected the immunostaining of G601S- and F805C-Kv11.1 protein differently. Incubating cells in MG132 minimally impacted G601S-Kv11.1 immunostaining, but it dramatically increased the diffuse immunostaining of F805C-Kv11.1 protein in the transitional ER. Similar results were seen after incubating cells in the proteasome inhibitor lactacystin. Differences in the cellular distribution of G601S-Kv11.1 and F805C-Kv11.1 protein persisted in transfected human inducible pluripotent stem cell derived cardiomyocytes. These are the first data to visually demonstrate mutation-specific differences in the trafficking-deficient LQT2 phenotype, and this study has identified a novel way to categorize trafficking-deficient LQT2 mutations based on differences in intracellular retention.